Thailand as a World Top Tourism Destination: Balancing Growth with Environmental and Cultural Preservation - Sriwapee, Kanokwan; Kenaphoom, Sanya; Ruangchai, Netnapa; Insumran, Yuwadee; Pawala, Thanyachanok; Jumroenpat, Paripon; Kaewlamai, Somboon (International Journal of Multidisciplinary in Management and Tourism, 2025)
Thailand has long been regarded as one of the top travel destinations in the world because of its stunning natural surroundings, rich cultural legacy, reasonable prices, and friendly people. The tourism industry employed millions of people and made up close to 20% of the country’s GDP before the COVID-19 pandemic. But this quick expansion has also brought with it a number of serious problems, such as overtourism, cultural commodification, infrastructure hardship, and environmental deterioration. The purpose of this study is to investigate how Thailand strikes a balance between environmental preservation, cultural preservation, and tourism-driven economic growth. Additionally, it aims to assess policy frameworks, pinpoint new issues, and showcase successful case studies in sustainable tourism. The research uses a documentary approach, and the study examines secondary sources, including academic papers published between 2015 and 2024, official reports (such as those from the Ministry of Culture and the Tourism Authority of Thailand), and documents from international organizations (such as UNESCO and the UNWTO). It compares example studies such as Mae Kampong’s community-based tourism, Maya Bay, and Chiang Mai Old Town. The results found that through programs like the Bio-Circular-Green (BCG) Economy Model, eco-certifications, waste reduction campaigns, and cultural heritage protection, Thailand is proactively moving toward more sustainable tourism, according to the research. While governmental initiatives like Vision 2030 are in line with international sustainability frameworks, case studies show effectiveness in environmental recovery and community empowerment. In conclusion, long-term resilience requires continued efforts in policy innovation, local participation, and adaptive management, notwithstanding Thailand’s significant achievement in tackling issues related to tourism. Other countries that rely on tourism and want to strike a balance between sustainability and growth might learn a lot from Thailand’s integrated strategy.